2021
DOI: 10.1002/iid3.442
|View full text |Cite
|
Sign up to set email alerts
|

Tranglutaminase 2 contributes to the asthmatic inflammation by modulating activation of alveolar macrophages

Abstract: Background Transglutaminase 2 (TG2), a multifunctional calcium‐dependent acyltransferase, is upregulated in asthmatic airways and reported to play a role in the pathogenesis of allergic asthma. However, the underlying mechanism is not fully understood. Objective To investigate the role of TG2 in alternative activation of alveolar macrophages by using murine asthma model. Methods TG2 expression was assessed in induced sputum of 21 asthma patients and 19 healthy controls, and lung tissue of ovalbumin (OVA)‐induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Moreover, the in vitro studies also verified that OS suppressed the proliferation and polarization of CD11b + M2 macrophages by reducing TGM2 expression. Previous studies also demonstrated that TGM2 mediated the polarization of M2 macrophage and cell proliferation, 17,52 further supporting the findings obtained in our investigation. Interestingly, the reduced number of infiltrated M2 macrophages and inhibited M2 polarization might contribute to the suppression of RA‐ILD 53 .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the in vitro studies also verified that OS suppressed the proliferation and polarization of CD11b + M2 macrophages by reducing TGM2 expression. Previous studies also demonstrated that TGM2 mediated the polarization of M2 macrophage and cell proliferation, 17,52 further supporting the findings obtained in our investigation. Interestingly, the reduced number of infiltrated M2 macrophages and inhibited M2 polarization might contribute to the suppression of RA‐ILD 53 .…”
Section: Discussionsupporting
confidence: 92%
“…Asthma is worsened by inflammation, which also causes the release of Th2 cytokines, including IL-4 and IL-13, that subsequently stimulate the development of M2 macrophage markers [40,41]. Many M1 macrophages are found in asthma patients, and reducing M1 macrophages and increasing M2 macrophages is one way to treat asthma [42]. In 2022, Gong et al demonstrated that luteolin increased M2 polarization and decreased M1 polarization in macrophages that had been stimulated by THP-1.…”
Section: Asthmamentioning
confidence: 99%
“…Asthma is generally associated with enhanced type 2 immune responses, including increased production of IL-4, IL-5, IL-13, CCL17 and CCL22 (23)(24)(25). Therefore, the generation of IL-4, IL-5, IL-13, CCL17 and CCL22 in BALF was detected.…”
Section: Ial Inhibits Ova-induced Generation Of Type 2 Cytokinesmentioning
confidence: 99%
“…IAL inhibits alternatively activated macrophages in vitro. it is well established that alternatively activated M2 macrophages, induced by IL-4, serve an important role in asthmatic inflammation (24). Arg-1 and Ym-1 are expressed by alternatively activated macrophages during asthmatic inflammation (26) and ccl17 and ccl22 are the main chemokines involved in eosinophil recruitment (7).…”
Section: Ial Inhibits Ova-induced Generation Of Type 2 Cytokinesmentioning
confidence: 99%